PENGEMBANGAN SISTEM INFORMASI DATA ALUMNI SISWA PADA SMK NEGERI 1 GORONTALO BERBASIS ANDROID - Jorry karim (JSAI (Journal Scientific and Applied Informatics), 2020)
Every educational institution annually graduates its alumni after undergoing a 3-year school period. From year to year, every new student acceptance will be the release of alumni to proceed to a higher level or jump to the world of work. Communication with alumni is not easy, usually, after graduating from school, alumni will be busy with their new activities. Until now, SMK Negeri 1 Gorontalo has not utilized the use of information systems in the collection and search of alumni. The method used in this research is the waterfall method, which is a systematic classical model to build software. The research was concluded that the information system that developed can be a solution to the problem of alumni data difficulties and save space in archive storage because alumni data is stored in the database.